The Effectiveness of IMD Implementation on Infant Weight Gain at The Kolelet Health Center Lebak Banten in 2022 - Apipah Apipah; Mariyani Mariyani (Pusat Riset dan Inovasi Nasional, 2022)
Background: The low level of breastfeeding in the first hour after birth and exclusive breastfeeding resulted in stunted growth of the baby, especially the weight and length of the baby. The government's first step in an effort to improve the health status of infants is to implement early initiation of breastfeeding (IMD). The results of a preliminary study on 4 infants who experienced an increase in body weight of 150-250 grams were previously carried out by IMD. Objective: Knowing the effectiveness of the IMD implementation on infant weight gain at the Kolelet Health Center Lebak Banten in 2022. Methodology: This research is quasi-experimental research with one-group pretest-posttest design method. The sample in this study were babies born at the Kolelet Health Center Lebak Banten in June 2022 as many as 30 respondents with a total sampling technique. The data were analyzed using the Paired sample t-test before the normality test was carried out. Results: The results of the univariate analysis showed that the baby's weight before the IMD was done on average = 2,965.00 grams and after the IMD was done the average = 3,333.67 grams so that an average difference was found of 368.67 grams. The results of the bivariate analysis showed that there was an effectiveness of the IMD implementation on the baby's weight gain with p = 0.000. Conclusions and Suggestions: The implementation of IMD is effective in increasing the baby's weight. Maternity mothers and their families are expected to increase their knowledge about the importance of IMD in order to increase their awareness in carrying out IMD to their babies and make mothers motivated to continue giving their breast milk without additional food so that the growth and development of babies can grow optimally and mothers avoid postpartum hemorrhage.